Evaluation of Standardized Instruments for Use in Universal Screening of Very Early School-Age Children: Suitability, Technical Adequacy, and Usability. (March 2018) - Miles, Sandra; Fulbrook, Paul; Mainwaring-Mägi, Debra
Universal screening of very early school-age children (age 4-7 years) is important for early identification of learning problems that may require enhanced learning opportunity. In this context, use of standardized instruments is critical to obtain valid, reliable, and comparable assessment outcomes. A wide variety of standardized instruments is available for screening and assessment purposes, though previous reviews have revealed some technical inadequacies. Suitability and usability of instruments should be considered as well as technical adequacy, making instrument selection a challenge for education professionals. This review used a systematic search to identify 48 instruments that measured development and early academic skills in very early school-age children. Instruments were evaluated and mapped against established psychometric and usability criteria, and rated as good, adequate, or not adequate. The results provide education professionals with a guide to selection of standardized instruments suitable for this age group and assessment purpose.